Which antidiabetic drugs do patients of T2DM prefer in India and why? A discrete choice experiment - Shrutangi Vaidya; Shubham Atal; Rajnish Joshi (Journal of Family Medicine and Primary Care)
Background: Uncontrolled diabetes persists despite guideline-based treatment, partly attributed to inadequate patient involvement. This research addresses shared decision-making by eliciting patient preferences in Type 2 Diabetes Mellitus (T2DM) treatment based on certain key attributes and explores their correlation with socio-demographic-clinical profiles. Methods: A discrete choice experiment (DCE) was conducted among T2DM outpatients in an Indian tertiary care center. A choice card was developed using the contextual choice framework, having six second-line antidiabetic drugs (ADs) from different classes incorporating seven attributes. Face-to-face interviews were conducted with patients, and elicited preferences were analyzed using descriptive statistics, Chi-square analysis, and multinomial logistic regression. Results: Out of the 87 evaluated participant choices, the most preferred drug was Glimepiride (51.7%), followed by Dapagliflozin (22.9%) and Teneligliptin (17.2%). Overall, the most important attributes were the effect on weight (29%), followed by route of administration (24%), and additional benefits offered by the drug (18%). Significant associations were found between participants’ drug preferences and their age (P = 0.002), socioeconomic status (P = 0.04), occupation (P = 0.004), and monthly income (P = 0.03). Age was not a significant predictor of drug choice for any of the drugs. Multinomial logistic regression showed that the overall model was statistically significant (P = 0.025), and it correctly predicted drug choice for 58.6% of the participants. Conclusion: Glimepiride was the most preferred option overall while the effect on weight was the most important attribute for patients in determining their preference. The study highlighted the importance of shared decisions and can guide practitioners in considering patient preferences when prescribing antidiabetic drugs.